A Bibliometric Analysis of the International Dental Journal (2011-2020) - Frank Mayta-Tovalino; Carlos Quispe-Vicuña; Miguel Cabanillas-Lazo; Arnaldo Munive-Degregori; Maria Eugenia Guerrero; Roman Mendoza (International Dental Journal, 2023)
Introduction: Bibliometrics is an area that allows for the evaluation of scientific publications by means of different indicators. The aim of this research was to perform a bibliometric study of the scientific production of the International Dental Journal (IDJ) between 2011 and 2020. Methods: All publications of the journal between 2011 and 2020 extracted from the Scopus database were included. The number of publications, most productive institutions, type of collaboration, most productive countries, most cited articles, and authors with the highest academic production were used as bibliographic indicators. It was exported to the SciVal tool for analysis. Results: A total of 630 documents published in IDJ by 1947 authors were collected, with a total of 7212 citations (11.4 citations per document). The United States was the country with the highest number of documents (100). The University of Adelaide (Australia) was the institution with the highest scientific production (16 publications), whilst the institution with the highest impact was the Universidade de São Paulo (Brazil), with 12.2 citations per paper. Marc Luiz Tennant was the author with the highest number of published manuscripts (13). Finally, most of the publications had international collaboration (146 documents). Conclusions: IDJ is a high-quality journal and, in the dental field, it has a high impact worldwide, which allows for a greater number of citations of its articles and placing it in the forefront of future research.